Quo vadis universitas? Remarks, comments and questions (non?) Pedagogical - Levovitski Tadeush (Borys Grinchenko Kyiv Metropolitan University, 2015)
The transformation of social and economic system and the integration of Poland with European Union have brought many positive chances. Simultaneously, some negative processes have intensified (also accompanied by new ones), which makes difficult the functioning and development of higher education. These negative processes and their noticeable results are presented in the article. Apart from critical opinions and questions about the direction of changes in higher education, some suggestions of improvements are included in the text of article.